Managing e-government projects : concepts, issues and best practices - Aikins, Stephen Kwamena (Hershey PA : Information Science Reference, 2012)
"This book collects the work of some of the best scholars and practitioners in the fields of e-government and project management, who explore how e-government projects can be managed, planned, and executed with effective project management techniques and methodologies"--Provided by publisher.
"Premier reference source"--Cover.
Includes bibliographical references and index.
Keywords: Internet in public administration -- Case studies; Public administration -- Information technology -- Case studies